Chemical screening and development of novel gibberellin mimics. Issue 16 (15th August 2017) - Jiang, Kai; Shimotakahara, Hiroaki; Luo, Ming; Otani, Masato; Nakamura, Hidemitsu; Moselhy, Said Salama; Abualnaja, Khalid Omer; Al-Malki, Abdulrahman Labeed; Kumosani, Taha Abduallah; Kitahata, Nobutaka; Nakano, Takeshi; Nakajima, Masatoshi; et al.
Graphical abstract: Abstract: Gibberellin (GA) plays versatile roles in the regulation of plant growth and development and therefore is widely used as a regulator in agriculture. We performed a chemical library screening and identified a chemical, named 67D, as a stimulator of seed germination that was suppressed by paclobutrazol (PAC), a GA biosynthesis inhibitor. In vitro binding assays indicated that 67D binds to the GID1 receptor. Further studies on the structure–activity relationship identified a chemical, named chemical 6, that strongly promoted seed germination suppressed by PAC. Chemical 6 was further confirmed to promote the degradation of RGA (for repressor of ga1-3 ), a DELLA protein, and suppress the expression levels of GA3ox1 in the same manner as GA does. 67D and its analogs are supposed to be agonists of GID1 and are expected to be utilized in agriculture and basic research as an alternative to GA.